The structure of physical conditioning of skilled footballers on the training stage to higher progress. - Karpa Igor' Yaroslavovich (Kharkov National Pedagogical University, 2011)
There are presented the results of monitoring of physical training of skilled players of different playing roles. The study included players aged 18-21 years who are at the stage of preparation for higher achievements. Data to determine the level of physical conditioning of skilled footballers such physical qualities as: the starting, the absolute and distant speed, speed-strength, general endurance and speed. There are established the dynamics of growth rates of physical qualities of skilled players in the preparatory period. There are found out the differences of physical conditioning indicators of the structure of skilled players according to the specific playing roles.